Diagnóstico de clima laboral y propuesta de plan de acción, en el área administrativa del grupo MB (Mayflower – Buffalos), a realizarse en el período septiembre 2016 –noviembre 2016 - Catota Guaman, Katherine Liliana (2017)
The current work climate is fundamental in the organizations development because it can be managed through: improvement, skills, knowledge, satisfaction and motivation of each of the collaborators. This project was specifically carried out in the administrative area, which one contained direct actors of this study, and it was considered important to carry out the work climate evaluation, since this type of evaluation had not been done and it is important to know the level of ownership, satisfaction and perception of each one of the collaborators close to the management maintained by the MB Group. In order to obtain the necessary information, a measuring instrument developed with the human resources area and natural observation of the daily activities developed by the collaborators. This instrument is the labor climate test that is socially known and easily accepted. Seven factors were considered: interpersonal relations, working conditions, communication, development, teamwork, leadership and supervision and remuneration. Administrative area and allowed to obtain general data. With the analysis of results, the required information was raised that contributed to the organization's strengths and weaknesses, there were weak factors such as: remuneration that is considered a fundamental factor for the satisfaction of each of the workers, but also strengths such as teamwork that allows activities to be carried out efficiently, in this way it is considered that It is necessary to generate a proposal of action plan that will allow to convert the weak points into strong ones.